Revision surgery for lumbar hemivertebra in a 7-year-old child with 10-year follow-up—a case report: A CARE-compliant article. Issue 48 (December 2017) - Xue, Xuhong; Zhao, Sheng
Abstract: Rationale: Hemivertebrae, which are the most frequent cause of congenital scoliosis, pose a challenge in terms of prognosis and therapy. The current gold standard treatment congenital scoliosis due to a lumbar and thoracic hemivertebra would be hemivertebra resection and short level posterior spinal fusion. Paucity literatures are reported for the treatment of hemivertebra by convex fusion with posterior hemivertebra excision. Patient concerns: The patient was first noticed to have a spinal problem at 7 years of age. A radiograph showed two full segment hemivertebra respectively at T10, between L4 and L5, with the spine deviating to the right side. No treatment was given, but he was followed with serial radiographs. At the 15 month follow up, a surgery was performed due to scoliosis progression, consisting of a unilateral instrumentation from L4 to L5 without hemivertebrectomy or epiphysiodesis. One year after surgery, the thoracic curve became larger and larger and hump started to progress as he grew. Diagnoses: Congenital scoliosis; Full segment hemivertebra at T10 and L4/5. Interventions: The full segment hemivertebra between L4 and L5 was excised and fusion in revision procedure. Transpedicular screws were inserted on the convex side in L4 and S1 and a rod was applied. A chart and radiological review were record at 8 years after final surgery. Outcomes: Eight years after the final surgery, the patient was completely pain-free, motion of the lumbar spine was preserved and the physiological curvatures were maintained. Good coronal and sagittal alignment of the spine was observed clinically and radiographically. Lessons: In summary, our case showed that unilateral instrumentation without hemivertebrectomy can result in an unacceptable deformity. However, the excellent outcome can be achieved when hemivertebra was excised. Although this is only a single case, the good result with a long follow-up suggests the technique is worthwhile for very young children with lumbosacral hemivertebra. Early recognition and resection combined with limited fusion were needed for these patients.